2016
DOI: 10.1016/j.bbmt.2016.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Busulfan-Based Myeloablative Conditioning Regimens Prior to Hematopoietic Cell Transplantation for Hematologic Malignancies

Abstract: Busulfan (Bu)-containing regimens are commonly used in myeloablative regimens prior to allogeneic hematopoietic cell transplantation (HCT). Yet, there is considerable variability on how Bu is administered related to frequency (four times a day, Q6 or daily, Q24) and the combination with other chemotherapeutic agents (cyclophosphamide, Cy or fludarabine, Flu). A prospective cohort study of recipients of Bu-based conditioning according to contemporary practices was used to compare different approaches in using B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 34 publications
2
12
1
Order By: Relevance
“…We considered 7 factors, including patient characteristics (age, sex, PS, and underlying diseases), and transplantation procedures (conditioning regimens, and donor-recipient relation), in the matching process, and all factors were well balanced between the 2 groups (Table 1). As in previous studies [9,10], there was no difference in OS, DFS, RR, or NRM between the 2 groups in the present study. The incidence of GVHD was also similar.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…We considered 7 factors, including patient characteristics (age, sex, PS, and underlying diseases), and transplantation procedures (conditioning regimens, and donor-recipient relation), in the matching process, and all factors were well balanced between the 2 groups (Table 1). As in previous studies [9,10], there was no difference in OS, DFS, RR, or NRM between the 2 groups in the present study. The incidence of GVHD was also similar.…”
Section: Discussionsupporting
confidence: 83%
“…Their group showed similar estimated daily AUC, OS, and NRM. Recently, Pasquini et al [10] reported the results of a prospective cohort study based on data from the Center for International Blood and Marrow Transplant Research. In that study, 4 cohorts were compared, including ivBU1 combined with Flu or CY and ivBU4 combined with Flu or CY.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…52 Seizure can manifest as encephalopathy resulting from either an electrolyte disturbance or from drug itself such as high dose busulphan. 53,54 Partial complex seizures may present only as confusion and can be prolonged from non-convulsive status epilepticus which is detectable only by EEG. Seizures may also occur with intrathecal administration of any drug including methotrexate, cytarabine, thiotepa, steroids, or rituximab.…”
Section: Confusion: Indirect Relation To Cancer Treatmentmentioning
confidence: 99%